Targetoid hemosiderotic melanocytic nevus. - Milano, A. (European Journal of Pediatric Dermatology, 2017)
This case demonstrates what happens when a hemorrhage occurs within a neoformation; it swells by the presence of blood inside it and takes a brownish color; when the extravasated blood runs out of the neoformation, it forms in the surrounding skin a concentric ring, initially attached to the neoformation itself. Subsequently, the internal hemorrhage is re-assimilated leading to flattening of the neoformation that reassumes its former appearance or by breaking the roof gives rise to a blood crust as in the present case. The hemorrhage of the perilesional skin tends to spread centrifugally and to heal starting from the center. This is why later on originates a targetoid appearance formed by the central neoformation, a normal skin ring and even more peripheral a hemorrhagic halo. Hemorrhage can occur in a lymphangioma, an angioma, a nevus or another neoformation (1, 2).